Hasanuddin Economics and Business Review: Foreword for the Inaugural Journal Volume - Julia Connell; Abdullah Sanusi (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2017)
We are pleased to write the foreword to the inaugural Journal Volume of the Hasanuddin Economics and Business Review (HEBR). The HEBR is an initiative of the Faculty of Economics and Business, University of Hasanuddin. There will be three volumes published per year covering a range of topics from the key elds of: business; economics and management.Â